Peran Elit Adat dalam Pemilihan Kepala Daerah Kabupaten Buru Tahun 2017 [The Role of Indigenous Elites in The 2017 Regional Head Elections in Buru Regency] - Tuhulele, Ahmad Bilal; Yunanto, Sri (Jurnal Politica, 2022)
The traditional elite in the 2017 Buru Regency Head Election has a strategic position for the survival of democracy for five years. The influence and power they have are the keys to the democratic process of the 2017 Pilkada won by the couple Ramli Umasagi and Amustofa Besan (RAMA). This study seeks to understand the existence of local elites on Buru Island and their roles in the 2019 Regent Election. Using the elite theoretical framework proposed by Mosca (1939), Pareto (2011) and Keller (201), synthesized with the theory of political participation formulated by Miriam Budiardjo (Budiardjo,1984), Samuel P. Huntington and Joan Nelson (Huntington and Nelson in Budiardjo,1984), this study finds: First, In the Buru Island community, the local elite has been stratified in the structure; Mat Gugul, Hinolog, and Soa. The figures in this elite not only played a role in social, cultural, and economic functions but also had an increasingly significant political role during the reform period. Second, In the 2017 Pilkada, these elites have carried out intense participation, among others, in conducting political socialization, being the Pilkada committee, mobilizing lower-level constituencies so that the community participates in politics and not abstaining, resolving conflicts if they occur and providing political supports to RAMA candidates who triumphed in this election. This research strengthens theories about the role of local elites or non-governing elites in the political process. Therefore, theoretically, the democratic process should pay attention to the role of local elites who have been proven to have an influence as evidenced in this study.AbstrakElite adat dalam Pemilihan Kepala Daerah (Pilkada) Kabupaten Buru Tahun 2017 memiliki posisi yang cukup strategis bagi kelangsungan demokrasi lima tahunan. Pengaruh dan kekuasaan yang mereka miliki menjadi kunci dalam proses demokrasi Pilkada 2017 yang dimenangkan oleh pasangan Ramli Umasagi dan Amustofa Besan. Penelitian ini ingin memahami eksistensi elit lokal di Pulau Buru dan perannya dalam Pemilihan Bupati 2019. Dengan menggunakan kerangka teori elit yang dikemukakan oleh Mosca (1939), Pareto (2011) dan Keller (2011) yang disintesakan dengan teori partisipasi politik yang dirumuskan oleh Samuel P. Huntington dan Joan Nelson (Huntington dan Nelson dalam Budiarjo,1984), penelitian ini menghasilkan temuan berikut ini: Pertama, dalam komunitas Pulau Buru, elit lokal telah terstratifikasi dalam struktur; Mat Gugul, Hinolog dan Soa. Tokoh-tokoh dalam elit ini tidak hanya berperan dalam fungsi –fungsi social, budaya dan ekonomi, namun juga mempunyai peran politik yang semakin signifikan dalam masa reformasi. Kedua, khusus dalam Pilkada 2017, para elit ini telah melakukan partisipasi yang inten antara lain dalam melakukan sosialisasi politik, menjadi panitia Pilkada, melakukan mobilisasi tingkat bawah agar masyarakat berpartisipasi dalam politik dan tidak Golput, menyelesaikan konflik jika terjadi dan memberikan dukungan politik kepada kandidat RAMA yang akhirnya mememangkan Pilkada ini. Penelitian ini secara teoritik memperkuat teori-teori tentang peran elit lokal atau elit yang tidak memerintah dalam proses politik. Oleh karena itu secara teoritik proses demokrasi seharusnya memberikan perhatian kepada peran elit lokal yang sudah terbukti memberikan pengaruh sebagaimana dibuktikan dalam penelitian ini.